A variant associated with sagittal nonsyndromic craniosynostosis alters the regulatory function of a non‐coding element. Issue 11 (6th October 2017) - Justice, Cristina M.; Kim, Jinoh; Kim, Sun‐Don; Kim, Kyunhgho; Yagnik, Garima; Cuellar, Araceli; Carrington, Blake; Lu, Chung‐Ling; Sood, Raman; Boyadjiev, Simeon A.; Wilson, Alexander F.
Abstract : Craniosynostosis presents either as a nonsyndromic congenital anomaly or as a finding in nearly 200 genetic syndromes. Our previous genome‐wide association study of sagittal nonsyndromic craniosynostosis identified associations with variants downstream from BMP2 and intronic in BBS9 . Because no coding variants in BMP2 were identified, we hypothesized that conserved non‐coding regulatory elements may alter BMP2 expression. In order to identify and characterize noncoding regulatory elements near BMP2, two conserved noncoding regions near the associated region on chromosome 20 were tested for regulatory activity with a Renilla luciferase assay. For a 711 base pair noncoding fragment encompassing the most strongly associated variant, rs1884302, the luciferase assay showed that the risk allele (C) of rs1884302 drives higher expression of the reporter than the common allele (T). When this same DNA fragment was tested in zebrafish transgenesis studies, a strikingly different expression pattern of the green fluorescent reporter was observed depending on whether the transgenic fish had the risk (C) or the common (T) allele at rs1884302. The in vitro results suggest that altered BMP2 regulatory function at rs1884302 may contribute to the etiology of sagittal nonsyndromic craniosynostosis. The in vivo results indicate that differences in regulatory activity depend on the presence of a C or T allele at rs1884302.